Bract size enlargement and longevity of bougainvillea spectabilis as affected by GA 3 and phloemic stress - Saifuddin, M.; Moneruzzaman, K.M.; Osman, Normaniza; Hossain, A.B.M.S. (2009)
A field experiment was conducted to assess the effect of gibberellic acid (GA 3100 and 150 ppm), phloemic stress and combination of 100 ppm GA 3 and phloemic stress on Bougainvillea bract blooming, expansion, development and bract longevity under exposed sun light condition (400-700 μEm -2 sec -1). A seven-years-old Bougainvillea plant was used in this experiment. Fifteen selected brunches were applied with 100, 150 ppm GA 3, phloemic stress, 100 ppm GA 3+phloemic stress and water control. The results showed that 100 ppm GA 3 increased the length of petiole, bract size and shape by 40%. Bract blooming was three days earlier in 100 ppm GA 3 treated branches and 4 days earlier in 150 ppm GA 3 than in water control. Bract longevity (required days from bract initiation to abscission) was higher for 4 in phloemic stress and for 2 days in 100 ppm GA 3+phloemic stress than in water control. However, bract longevity was shorter in 100 and 150 ppm GA 3 than in control. The number of bracts per branch was higher in 100 ppm GA 3+phloemic stress and phloemic stress than the other treatments. Petal size and petiole length were the highest in 100 ppm GA 3. But there were no significant changes in bract size and color development in phloemic stress. Maximum chlorophyll fluorescence was observed in phloemic stress. Quantum yield (F√Fm) was higher in phloemic stress and 100 ppm GA 3+phloemic stress than in other treatments. The findings suggested that gibberellic acid played an important role to induce rapid bract blooming and expansion whereas, phloemic stress increased total number of bract and longevity. © 2009 Asian Network for Scientific Information.